Skeletal Bimaxillary Protrusion: Combined Surgical and Orthodontic Approach – A Case Report - Subrat Kumar Padhiary; Kanhu Charan Sahu; Gunjan Srivastava; Harsh Mohan Pathak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Bimaxillary protrusion is one of the commonly seen skeletal deformity in Indian population. This skeletalcondition is typically characterized by proclined and protruding anterior teeth with everted lips. If thiscondition is associated with macroglossia or any parafunctional habits like tongue thrusting or thumbsucking, an anterior open bite is often found. Minor discrepancies can be managed by orthodontic treatmentalone by extracting all first premolars and retracting the anterior segment. But in severe skeletal cases,orthognathic surgery along with pre-and post-surgical orthodontics is the best option to get the ideal result.This article describes the case of a female patient with bimaxillary protrusion. The patient had a convexprofile, anterior open bite, and incompetent lips. Chin had a relative deficiency with hyperactive mentalismuscle. On patients’ consent and willingness for a shorter course of the treatment period, surgery firstapproach was planned. Within seven months of the total treatment period, a remarkable change in facialprofile and a pleasing anterior occlusion was achieved.